Dispositional and situational moral emotions, bullying and prosocial behavior in adolescence - Oriol, Xavier (2021)
Studies that distinguish the role of dispositional and situational moral emotions in bullying situations remain limited in the international literature. This work, therefore, aims to analyze the role of dispositional and situational moral emotions in bullying and prosocial behavior in adolescents. Two studies were conducted: a cross-sectional study including 644 adolescents aged 14–18 years (M = 15.6, DT = 1.4) and a repeated measures design including 235 adolescents aged 10–15 years (M = 12.5, DT = 0.9). The objectives of Study 1 were 1) to validate two scales for the situational moral emotions elicited in bullying situations (elevation and moral disgust) and 2) to examine the relationships between dispositional and situational moral emotions and prosocial behavior toward victims and bullying behavior. The results show adequate psychometric properties for both elevation and moral disgust scales. Furthermore, both situational moral emotions are negatively related to bullying behavior, whereas dispositional emotions such as compassion and gratitude have a positive effect on prosocial behavior. Study 2 assessed the prospective relationship between dispositional gratitude and prosocial behavior toward victims and bullying behavior. The results of this study indicate that dispositional gratitude has a positive prospective effect on prosocial behavior towards victims and a negative effect on bullying behavior. In conclusion, the relevance of moral emotions for the prevention of bullying behavior is highlighted and the role that self-transcendent dispositional emotions have on prosocial behavior from the perspective of developmental psychology.